Improving Science Learning Outcomes Through the Peer Tutor Method in Class IV Students of SDN 2 Tigajuru - Ulya, Himatul (Universitas Sebelas Maret, 2022)
Science learning in principle teaches students to always try. Students should be interested in learning science because basically there is a lot of knowledge that needs to be known. One way to be able to know this knowledge is to be enthusiastic in learning science, which of course requires teacher creativity in teaching. Therefore, science should be taught not only through the lecture method but can be taught through other methods that are more interesting and arouse students' enthusiasm in learning. The same problem also occurs in class IV of SDN 2 Tigajuru, Mayong District, Jepara Regency. Based on preliminary observations conducted on October 1, 2016, the number of students in class IV of SDN 2 Tigajuru, Mayong Subdistrict, Jepara Regency is 15 students. One of the appropriate learning methods to realize a participatory learning situation is the use of the peer tutor method. This research is a type of classroom action research